Biomonitoring through the laboratory evaluation of a population exposed to ores - Silvia Eline Alfaia Lima; Amanda Furtado de Almeida; Roberto Messias Bezerra; Francinaldo Sarges Braga; Beatriz de Oliveira Azevedo; Wentony Mark Costa Milhomen; Alicia Karine Pereira da Silva; Maitê Amanajás Viana; Odirlei Santos Moreira; Deyse de Souza Dantas; Madson Ralide Fonseca Gomes (São Paulo State University (UNESP), 2020)
The mineral exploration in the Amazon, has determined impacts for the environment and for the populations exposed to different agents of the production process. The extraction and the beneficiation developed in the state of Amapa left environmental damages and issues that influence the population´s health, such as contamination by metals. Researches have shown that some forms of metals are toxic; causing neurological and genetic complications. The present work considers the toxicological evaluation a fundamental prerequisite in the identification of potential damages to the health. Accordingly, the study´s objective is the investigating of the toxic effects through laboratory analysis in a population group of the Elesbao district in Santana-AP municipality exposed to residues of minerals and metals. In this way, the amount of metals in Elesbao´s water region was evaluated by spectrophotometer, hematological and biochemical tests were accomplished for laboratory evaluation. The paired t-test was applied for statistical evaluation with a significance of 5% (p <0.05). It was concluded that iron and manganese are present in high concentrations in the region water. Hematological and biochemical exams presented statistically relevant alterations. Significant differences in the morphology of the cells were detected by microscopic analysis. This study demonstrates the importance of the investigation of sources of metal exposure and preventing the elimination and minimization of the risks of adverse effects to excessive exposure to multiple metals.